Implementasi wawasan Nusantara dalam berbagai aspek kehidupan di Indonesia - Ziah, Khalidah; Y, Fierly Sabila; Rahmanisa, Nabila Nur; Fidyati, Nur; Amrulloh, M. Fahmi (Maliki Interdisciplinary Journal, 2024)
Archipelagic insight is the way Indonesia views itself and its environment. It is an idea that emphasizes how important it is for Indonesia to unite in the face of globalization and focuses on increasing the self- awareness of the Indonesian people as a diverse and cultured nation. It aims to maintain the unity and integrity of the Indonesian nation and state and serve as a guideline for achieving national goals. Archipelago insight also serves as a motivation for the Indonesian people to increase their love for the country, so that their enthusiasm to participate in achieving national goals also increases. So that people not only understand the nature and concept of archipelago insight, but also voluntarily implement it in their daily lives in the nation and state. wawasan; Negara; implementasi; tujuan; globalisasi